STUDI PEMILIHAN JENIS ALAT ANGKUT BAHAN BAKAR MINYAK WILAYAH KEPULAUAN - Edwin Matatula (Fakultas Teknik Universitas Pattimura, 2019)
Abstrak Supplying fuel oil to the outermost and foremost islands, faced a relatively long distribution chain, especially in the most recent network to consumers on the island, many economic and technical problems. Economically, the people in the outermost islands, the foremost, have small-scale economic dynamics which causes relatively little oil fuel consumption. While technically, infrastructure support in supporting the supply process is very minimal. The fleet of ships as the main means of transporting fuel oil are people's vessels which are designed not specifically to transport liquid cargo. These vessels have relatively small types and dimensions, with very minimal safety equipment. The unavailability of ship dock facilities for loading and unloading so that the loading and unloading process is adequate on the island. Another thing is the geographical conditions of the scattered region and the influence of the weather, high sea waves in certain seasonswhich hinder transport activities. These constraints later caused the process of distribution of fuel oil to not run smoothly and there was a scarcity of inventory, even a vacancy occurred and triggered a surge in prices. The selection of fuel transportation equipment between the Tug-barge, Self Propelled Oil Barge and Tanker using the Analytic Hierarchy Process (AHP) approach, produces tug-barge as the main choice. Furthermore, operational planning is carried out by considering the demand quantity, shipping distance, operating conditions and regional characteristics.Pusher-Barge, which is offered in the Central Maluku Lease Islands, has a relatively high investment value, but there is a significant savings in the operating cost component of 54%, 78% sailing cost and 45,18% decrease in total transport costs per year current system.